2022
DOI: 10.1155/2022/2676114
|View full text |Cite
|
Sign up to set email alerts
|

The Dysregulation of SOX Family Correlates with DNA Methylation and Immune Microenvironment Characteristics to Predict Prognosis in Hepatocellular Carcinoma

Abstract: Background. Due to the molecular heterogeneity of hepatocellular carcinoma (HCC), majority of patients respond poorly among various of therapy. This study is aimed at conducting a comprehensive analysis about roles of SOX family in HCC for obtaining more therapeutic targets and biomarkers which may bring new ideas for the treatment of HCC. Methods. UALCAN, Kaplan Meier plotter, cBioPortal, STRING, WebGestalt, Metascape, TIMER 2.0, DiseaseMeth, MethSurv, HPA, CCLE database, and Cytoscape software were used to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 62 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…In addition to CXC12, SOX17 was also at the core of the PPI network. The SOX family is correlated with multiple clusters of immune cells and is involved in the regulation of the angiogenesis-related signaling pathway [ 26 ]. In one study, SOX17 was found to promote high-grade glioma by increasing vascular endothelial growth factor (VEGF) mediated vascular abnormality [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CXC12, SOX17 was also at the core of the PPI network. The SOX family is correlated with multiple clusters of immune cells and is involved in the regulation of the angiogenesis-related signaling pathway [ 26 ]. In one study, SOX17 was found to promote high-grade glioma by increasing vascular endothelial growth factor (VEGF) mediated vascular abnormality [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, SOX11 could promote brain metastasis in triple-negative breast cancer (TNBC) [ 41 ]. In hepatic cell carcinoma (HCC), higher mRNA transcript levels of SOX11 were associated with shorter OS and PFS [ 42 ]. However, it was reported that the upregulation of SOX11 expression might be a good prognostic factor for patients with MCL [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies also showed that SOX11 -positive MCL patients with lymph node involvement had a poorer prognosis [ 47 ]. In addition, high mRNA levels of SOX11 in HCC were closely associated with the high grade of the tumor [ 42 ]. In our study, SOX11 expression levels in ACC, COAD, ESCA, TGCT and UVM showed an increasing trend with increasing tumor stage, but the trend was more pronounced mainly in tumor stages I-III which might be due to the small sample size of stage IV patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor Immune Estimation Resource (TIMER, https://cistrome.shinyapps.io/timer/ ), an online tool for comprehensive analysis of tumor-infiltrating immune cells [ 24 ], was used to assess the correlation between ARID family genes and immune infiltrates. We followed the methods of Qin et al to perform the immune infiltrates correlation analysis [ 25 ]. The relationships of ARIDs expression with tumor-infiltrating immune cells (B cell, CD4 + T cell, CD8 + cell, macrophage, neutrophil, and dendritic cell) were identified by purity-corrected partial Spearman's correlation (partial-cor) and statistical significance, and the results were shown in scatterplots provided by TIMER.…”
Section: Methodsmentioning
confidence: 99%